EFEKTIVITAS SISTEM PENGELOLAAN PELAYANAN PENDAPATAN PEMERIKSAAN ALAT PEMADAM KEBAKARAN DI DINAS KEBAKARAN DAN PENANGGULANGAN BENCANA KOTA BANDUNG - Ridwan, Muhammad; Nugraha, Akmal Dwi (Jurnal Konstituen, 2023)
Fire extinguisher inspection services are services provided by the local government for inspection and testing of fire extinguishers, fire prevention, and fire disaster rescue that are used and managed by individuals or entities. However, in reality, service receipts for inspection of fire extinguishers in the city of Bandung from 2020 to 2022 have not reached the target.This study aims to determine the adequacy and elasticity in service revenue for fire extinguisher inspection in the city of Bandung, fairness in service income for inspection of fire extinguishers in the city of Bandung, and administrative capabilities in service income for inspection of fire extinguishers in the city of Bandung. The theory used in this study is the theory of mandatory criteria in assessing the effectiveness of an income service collection from Phaurela and Emy (2017) in which there are three criteria, namely (1) Adequacy and Elasticity, (2) Fairness, and (3) Administrative Capability. In this study using qualitative research methods with a descriptive approach. Data collection techniques used are interviews, observation, documentation, and literature study. Based on the results of the study, it can be concluded that the management of fire extinguisher inspection revenue services associated with three criteria, namely adequacy and elasticity, fairness, and administrative adequacy is considered ineffective. Criteria for administrative adequacy are not yet effective because the implementation is not in accordance with the appropriate technical and not easy to do and reach the target that has been set. There are several obstacles that occur in the process of managing fire extinguisher inspection revenue services and efforts are also found to resolve these obstacles. Keywords: Effectiveness, Supervision, Retribution, Bandung City Fire and Disaster Relief Office